Examining Students’ Perceptions of Accounting Education in Libya - Issa , Mohamed (Scientific Journal of University of Benghazi, 2021)
Students' perceptions have recently been used as a tool to improve education methods and to understand students. This study aimed to explore students' perceptions regarding accounting courses in Libya. Using a combined data set consisting of information on accounting education (the instructors' performance, the quality of the courses and the grading system). The data was collected from a random sample of students in Libyan universities and this data was analyzed by using descriptive statistics and one-way ANOVA. The study results showed that the students were satisfied with the instructors' performance, the quality of the courses and the grading system.